Recurrent retrobulbar optic neuritis in seronegative rheumatoid arthritis - Nordin, Mohammad Hudzaifah; Rosli, Abd Hadi; Abd Bari, Muhd Syafi; Masnon, Nurul Ain; Wan Hitam, Wan Hazabbah (Universiti Putra Malaysia Press, 2022)
Rheumatoid arthritis (RA) is a multisystemic autoimmune disease which can be associated with visual threatening ocular manifestations. Common ocular associations with RA include necrotising scleritis and peripheral ulcerative keratitis (PUK). Optic nerve involvement otherwise is uncommon, especially as a presenting feature of RA. We report a rare case of recurrent bilateral retrobulbar optic neuritis (ON) with progressive visual deterioration as an early manifestation of seronegative RA. This case posed diagnostic and management challenges due to its unusual presentation and initially inconclusive investigations. The patient was diagnosed with seronegative RA three years after the first eye presentation. Her RA disease activity score (DAS-28) improved after treatment with a disease-modifying anti-rheumatic drugs (DMARDs), and her ON attacks have been controlled since then. However, her visual acuity, visual field and colour vision remained poor after multiple ON attacks. Multidisciplinary care is key to managing such a patient’s condition and its potential disease complications.